Balance exercises as the basis for developing the level of physical and skill performance in basketball young players - Houssain Mahmoud, M. (World Journal of Sport Sciences, 2011)
Balance is one of the important abilities for basketball young players because of its use in man to man defense during the game. This requires that they have the ability to control their bodies to reduce committing legal faults and to protect them from falling on the ground when changing directions and rapid turning movements which may not fit in some positions with body position. The age from 10-12 years is the best stages for developing the ability of balance. Therefore, the research aimed at using balance exercises as a basis for developing the level of physical and skill performance for basketball young players. The researcher used the experimental method on two groups, one of them was a experimental and the other one is a control group. Each one consisted of 12 young players using pre- and post test. Statistical results indicated the existence of significant differences between the two groups of experimental and control groups in both the level of physical and skill performance in favor of the experimental group. In the light of the results, the researcher recommends incorporating balance exercises in the programs of young players' preparation and deriving them from motor components for basic skills.